Formulation and Evaluation of Chlorhexidine loaded Transethsomal gel - Verma, Suraj; Kumar, Sachin (Journal of Neonatal Surgery, 2025)
The current research emphases on the preparation and analyzing of a transethosomal gel loaded with chlorhexidine to enhance its dermal delivery and antimicrobial efficacy. Chlorhexidine, a broad-spectrum antiseptic, often suffers from poor skin permeability and retention in conventional formulations. To overcome these limitations, transethosomes ultra-deformable vesicle carriers made up of edge activators, phospholipids and ethanol were employed to encapsulate chlorhexidine using the thin-film hydration method. The formulated vesicles were placed into a Carbopol 934P-based gel to improve topical application and sustained release. Preformulation studies confirmed the physicochemical compatibility of chlorhexidine with selected excipients. The optimized transethosomal formulation (TE5) exhibited a particle size of 112 nm, zeta-potential of –26 mV, and high entrapment efficiency (80%). The transethosomal gel (TE5) displayed favorable organoleptic characteristics, pH (6.4±0.123), spreadability, viscosity, and extrudability. In-vitro drug release followed a controlled and sustained pattern, showing approximately 88.76 % release over 12 hours, fitting best with the First order model, indicating diffusion-controlled release. Stability studies confirmed the physicochemical stability of the formulation over two months. Overall, the chlorhexidine-loaded transethosomal gel demonstrated enhanced drug penetration, prolonged retention, and improved antimicrobial potential, offering a best strategy for skin delivery in dermal and wound care.